2014
DOI: 10.1007/s40291-014-0118-z
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Cellular RNA in Blood During Storage at Room Temperature: A Comparison of Cell-Free RNA BCT® with K3EDTA Tubes

Abstract: BackgroundMessenger RNA (mRNA) expression levels in blood cells are important in disease diagnosis, prognosis and biomarker discovery research. Accurate measurements of intracellular mRNA levels in blood cells depend upon several pre-analytical factors, including delays in RNA extraction from blood after phlebotomy. Dramatic changes in mRNA expression levels caused by delays in blood sample processing may render such samples unsuitable for gene expression analysis.ObjectivesThis study was conducted to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…An optimal assay should give the same result in repeat samples 100% of the time, although this is hard to achieve in all assays including robust clinical assays such as ER, PR and HER2 testing for breast cancer [ 8 ]. Few studies have assessed the reproducibility of ctDNA analysis [ 9 14 ], a major constraint on multi-centre studies and ultimately clinical adoption into using ctDNA as a diagnostic tool is the requirement under the current recommended standard practice for processing, which utilizes EDTA tubes, to process samples within hours of collection. This both adds potential variability in the processing of samples at individual sites, and necessitates expensive shipping of frozen samples to central analysis centers.…”
Section: Introductionmentioning
confidence: 99%
“…An optimal assay should give the same result in repeat samples 100% of the time, although this is hard to achieve in all assays including robust clinical assays such as ER, PR and HER2 testing for breast cancer [ 8 ]. Few studies have assessed the reproducibility of ctDNA analysis [ 9 14 ], a major constraint on multi-centre studies and ultimately clinical adoption into using ctDNA as a diagnostic tool is the requirement under the current recommended standard practice for processing, which utilizes EDTA tubes, to process samples within hours of collection. This both adds potential variability in the processing of samples at individual sites, and necessitates expensive shipping of frozen samples to central analysis centers.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 CfDNA BCT is also known to stabilize cell-free RNA in blood during storage and transport at room temperature for 3 days. [23][24][25] Previous studies also found that CfDNA BCT preserves and stabilizes spiked cancer cell lines in donor blood samples for at least 4 days at room temperature. 26 Results from analysis I indicated that the CfDNA BCT performs significantly better than the other 3 (EDTA, citrate, heparin) with the highest detection levels of rare cells and the lowest of total negative events.…”
Section: Discussionmentioning
confidence: 93%
“…As these BCTs were previously shown to preserve leukocytes and prevent the release of cellular RNA into plasma, even after over three days of storage at room temperature [20,24,25], our study compared commonly-used EDTA and Citrate tubes with BCTs in terms of the ability to preserve modelled CTCs (spiked cultured tumour cells) and of greater interest, cellular RNA.…”
Section: Discussionmentioning
confidence: 99%